If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4/3x-9=8-3/6x
We move all terms to the left:
4/3x-9-(8-3/6x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 6x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
4/3x-(-3/6x+8)-9=0
We get rid of parentheses
4/3x+3/6x-8-9=0
We calculate fractions
24x/18x^2+9x/18x^2-8-9=0
We add all the numbers together, and all the variables
24x/18x^2+9x/18x^2-17=0
We multiply all the terms by the denominator
24x+9x-17*18x^2=0
We add all the numbers together, and all the variables
33x-17*18x^2=0
Wy multiply elements
-306x^2+33x=0
a = -306; b = 33; c = 0;
Δ = b2-4ac
Δ = 332-4·(-306)·0
Δ = 1089
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1089}=33$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(33)-33}{2*-306}=\frac{-66}{-612} =11/102 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(33)+33}{2*-306}=\frac{0}{-612} =0 $
| 105-2.5x=85-2x | | s+(-3)=-11 | | 8x+7=3x+5 | | 11x-6+21x-6=180 | | 3(3x-2)=5(2x+1) | | -6x+2=4x-10 | | 1(-1y+5)=2 | | -2(x-4)-3(x+7)=-(x+5) | | 4x+5(2x-3)=9x-55 | | 2x+8x+1=8x+5+2 | | 1=0.4x-0.8x-35 | | 3x9=2x+5 | | 1000(8x-10)=40(920+100x) | | f+(-23)=-10 | | 18x-152=6x+184 | | 1.3x+1.79=0.4x+2.69 | | 1/2(3x-5)=2/6x-23 | | 3x+2+5x+5=5x+19 | | x/3−3/4=3x+4/12 | | 4(3x+6)=-48 | | 13j-10j-2j+3=14 | | t(4.9t-2.76)=0 | | 8x+4=3x+11 | | -(4x-4)-(5x-6)+2=-11(x-1)-(3x+12)+3 | | 2x+2(x+4)=380 | | -7x+9=3+49 | | 12n-11n=17 | | 4(3x+6=-48 | | 52x+12=10+4-1 | | -8s-3s=27 | | 7y-3y=4y | | 2/5(x-2)=7x-4 |